Towards a transmedia learning approach in ESL context - Rodrigues, Patrícia (2017)
Transmedia story worlds allow students to express themselves and take part in a shared culture while developing learning paths. Whilst the use of transmedia storytelling in formal learning environments has been steadily gaining ground among educators, documented cases of its application are still sparse. This paper reports on a transmedia learning storyworld targeted to English as Second Language students by providing insight on the design of the storyworld and analysis of its core elements. The potential and challenges of applying a transmedia approach in an educational setting are explored through the description of the imple- mentation of a prototype version of a transmedia learning storyworld and discussion of issues emerging from the application process. Based on the insights acquired during this stage, the paper concludes with a set of considerations to take into account in the development of future research in the transmedia learning field.